2021
DOI: 10.1111/1475-6773.13700
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for measuring spatial access to health care

Abstract: Objective To compare measures of spatial access to care commonly used by policy makers and researchers with the more comprehensive enhanced two‐step floating catchment area (E2SFCA) method. Study Setting Fourteen southwestern Pennsylvania counties. Study Design We estimated spatial access to buprenorphine‐waivered prescribers using three commonly used measures—Euclidean travel distance to the closest prescriber, travel time to the closest provider, and provider‐to‐population ratios—and the E2SFCA. Unlike other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Using metrics that incorporate population demand and measures of hospital capacity, this study raised concerns that using measures of travel distance or time alone might underestimate the proportion of the US population that experiences limitations in access to surgical care-using E2SFCA models, nearly 10% had low access to any surgical hospital, and 21% had low access to advanced-resource centers. This discordance aligned with our prior work 17 assessing spatial access to EGS hospitals in California and the recent findings of Drake et al, 9 who directly compared the E2SFCA with travel impedance measures of spatial access to buprenorphine prescribers and found that standard metrics (impedance measures and physician-to-population ratios) identified less than half of low-access census tracts compared with E2SFCA models.…”
Section: Discussionsupporting
confidence: 84%
“…Using metrics that incorporate population demand and measures of hospital capacity, this study raised concerns that using measures of travel distance or time alone might underestimate the proportion of the US population that experiences limitations in access to surgical care-using E2SFCA models, nearly 10% had low access to any surgical hospital, and 21% had low access to advanced-resource centers. This discordance aligned with our prior work 17 assessing spatial access to EGS hospitals in California and the recent findings of Drake et al, 9 who directly compared the E2SFCA with travel impedance measures of spatial access to buprenorphine prescribers and found that standard metrics (impedance measures and physician-to-population ratios) identified less than half of low-access census tracts compared with E2SFCA models.…”
Section: Discussionsupporting
confidence: 84%
“…These threshold drive times are broadly consistent with CMS Medicare Advantage network adequacy standards. 29 Next, we used an E2SFCA method 16,30 to measure geographic access to medical oncologists. The E2SFCA simultaneously accounts for provider capacity, patient demand, and travel time facing patients.…”
Section: Methodsmentioning
confidence: 99%
“…We provide a more detailed description of the E2SFCA approach and weighting in the technical appendix (Data S2). For further discussion of the E2SFCA measure, see Luo and Qi 16 and Drake et al 30 For further discussion of the weight approach, see Kwan, 31 Wang, 33 and Drake et al 30 We grouped RUCA codes into three categories of rurality: urban (RUCA codes 1-3), large town (RUCA codes 4-6), and rural (RUCA codes 7-10). We aggregated national ADI rankings of census block groups to the census tract level based on the mean rankings for census block groups within a census tract.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations